Involving patients in drug development for Neglected Tropical Diseases (NTDs): a qualitative study exploring and incorporating preferences of patients with cutaneous leishmaniasis into Target Product Profile development - Castro, María del Mar; Erber, Astrid C.; Arana, Byron; Cota, Gláucia; Denkinger, Claudia M.; Harrison, Nicole; Kutyi, Julia; López-Carvajal, Liliana; Plugge, Emma; Walochnik, Julia; Olliaro, Piero (PLoS neglected tropical diseases, 2024)
Background Target Product Profiles (TPPs) are instrumental to help optimise the design and development of therapeutics, vaccines, and diagnostics - these products, in order to achieve the intended impact, should be aligned with users’ preferences and needs. However, patients are rarely involved as key stakeholders in building a TPP. Methodology Thirty-three cutaneous leishmaniasis (CL) patients from Brazil, Colombia, and Austria, infected with New-World Leishmania species, were recruited using a maximum variation approach along geographic, sociodemographic and clinical criteria. Semi-structured interviews were conducted in the respective patient’s mother tongue. Transcripts, translated into English, were analysed using a framework approach. We matched disease experiences, preferences, and expectations of CL patients to a TPP developed by DNDi (Drug for Neglected Diseases initiative) for CL treatment. Principal findings Patients’ preferences regarding treatments ranged from specific efficacy and safety endpoints to direct and significant indirect costs. Respondents expressed views about trade-offs between efficacy and experienced discomfort/adverse events caused by treatment. Reasons for non-compliance, such as adverse events or geographical and availability barriers, were discussed. Considerations related to accessibility and affordability were relevant from the patients’ perspective. Conclusions/Significance NTDs affect disadvantaged populations, often with little access to health systems. Engaging patients in designing adapted therapies could significantly contribute to the suitability of an intervention to a specific context and to compliance, by tailoring the product to the end-users’ needs. This exploratory study identified preferences in a broad international patient spectrum. It provides methodological guidance on how patients can be meaningfully involved as stakeholders in the construction of a TPP of therapeutics for NTDs. CL is used as an exemplar, but the approach can be adapted for other NTDs.